(untitled) - Ferro, Cristina; Morrison, Amy C; Pardo, Raul; Tesh, Robert B; Torres, Mariela; Wilson, Mark L (Maryland, 1995)
Ecological studies on the sand fly Lutzomyia longipalpis (Lutz & Neiva) were conducted during 1990-1993 at a small rural community in Colombia where American visceral leishmaniasis is endemic. Weekly sand fly collections were made from pigpens, houses, an
Keywords: Lutzomyia longipalpis; Bibliografía del INS; Leishmaniasis visceral; Colombia